Let f: A → B and g : B → C be one  one functions. Then, gof: A → C is
If f : A → B and g : B → C be two functions. Then, composition of f and g, gof : A → C is defined a
1 Crore+ students have signed up on EduRev. Have you? Download the App 
f: R → R is defined by f(x) = x^{2}  2x + 1. Find f[f(x)]
Let f: Q→Q be a function given by f(x) = x^{2},then f^{ 1}(9) =
Let g(x) = 1 + x – [x] and
Then f{g(x)} for all x, is equal to:
Let f = {(1, 3), (2, 1), (3, 2)} and g = {(1, 2), (2, 3), (3, 1)}. What is gof(2)?
If ƒ(x) = tan^{1} x and g(x) = tan(x), then (gof)(x) =
If f: R → R and g: R → R defined by f(x) = 2x + 3 and g(x) = x^{2} + 7, then the value of x for which f(g(x)) = 25 is
204 videos288 docs139 tests

204 videos288 docs139 tests
